2021
DOI: 10.3390/su13052486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Human Utilization of Northern Snakehead (Channa argus Cantor, 1842) on the Settlement of Exotic Fish and Cladoceran Community Structure

Abstract: Empirical studies suggest that changes in the density of top predators, such as carnivorous fish, in freshwater food webs, strongly affect not only fish communities but also various primary and secondary consumers. Based on these findings, we explored how differences in the utilization of carnivorous fish (i.e., Northern Snakehead, Channa argus) by humans affected the fish and cladoceran community structure as well as the settlement of exotic fish species (i.e., Lepomis macrochirus and Micropterus salmoides) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 68 publications
0
11
1
Order By: Relevance
“…In this study, L. macrochirus consumed more cladocerans every spring than copepods; however, their choice changed to concentrated consumption of copepods in summer and autumn. Choi et al [63] suggested that the dominance of L. macrochirus in wetlands in this area may lead to the near extinction of pelagic cladocerans. Pelagic cladocerans have a relatively large body size and frequent movements, making them relatively easy for fish such as L. macrochirus to locate and capture.…”
Section: Winter As a Temporal Refugementioning
confidence: 94%
See 2 more Smart Citations
“…In this study, L. macrochirus consumed more cladocerans every spring than copepods; however, their choice changed to concentrated consumption of copepods in summer and autumn. Choi et al [63] suggested that the dominance of L. macrochirus in wetlands in this area may lead to the near extinction of pelagic cladocerans. Pelagic cladocerans have a relatively large body size and frequent movements, making them relatively easy for fish such as L. macrochirus to locate and capture.…”
Section: Winter As a Temporal Refugementioning
confidence: 94%
“…In this study, L. macrochirus, a dominant fish species in the Upo Wetlands, consumed more copepods and cladocerans than any other food source. Previous studies have also suggested that L. macrochirus is a representative planktivorous fish, which mainly consumes zooplankton [62,63]. Cladocerans, which have relatively poor swimming capabilities, are preferred by fish predators over copepods, which leads to rapid depletion of cladoceran populations in the field [62].…”
Section: Winter As a Temporal Refugementioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the cladoceran community and tet (A) gene in 20 riverine wetlands located in the mid-lower reaches of the Nakdong River from May to June 2019. Among the 40 wetlands studied by Choi and Kim [ 19 ], wetlands 1–20, where cladocerans were abundant, were selected as the survey site. Among the 11 L water samples collected from each wetland, 10 L were used for the quantification of cladoceran individuals, and the remaining 1 L was used to analyze the ARG.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we focused on the gene transfer of ARGs between bacteria and cladocerans. Cladoceran communities are primary consumers commonly distributed in various freshwater ecosystems that mainly consume bacteria and phytoplankton [ 18 , 19 ]. Furthermore, considering that cladocerans are frequently used as food sources for top predators such as fish and macroinvertebrates, the continuous accumulation of ARGs induced by cladocerans can be an important mediator of ARG proliferation and vertical transmission in freshwater environments.…”
Section: Introductionmentioning
confidence: 99%